L’introuvable Terra di u Cumunu ? Genèse, évolutions et perspectives des terres collectives de la montagne corse - Gilles Guerrini (Revue de Géographie Alpine)
The present-day collective lands of Corsica differ in their origin from those of the rest of France. Probably appeared in the Middle Ages, for the few specialists, historians, or ethnologists, who were interested in the evolution of the nature of island land, they would have disappeared in the 19th century. According to the thesis of this article, it is, on the contrary, currently that they are legally recognized. Indeed, the agreements of delimitation of forests between the state and the municipalities, known as the Blondel Transactions of 1852, lead to the legalization of indivision between each inhabitant of a community on wooded areas. From the 20th century on, the crisis of the island agro-pastoral economy saw the disappearance of certain collective lands, appropriated by municipalities and even individuals. At present, a few survivors still bear witness to the ancient community practices of the Corsican mountain. In an exceptional context of land disorder, the return to common practices of the land is perhaps a solution to combat the rural decline of the interior of the island.